A Compact UWB Slot Antenna with Reconfigurable Band-Notched Function for Multimode Applications - Musavand, Ali; Zehforoosh, Yashar; Ojaroudi, Hamed; Ojaroudi , Nasser (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel design of printed slot antenna with multiresonance and switchable band-notched performances is presented whose frequency characteristics can be reconfigured electronically to have both a single- or dual-band notch function. The presented antenna is reconfigurable to suppress unwanted interfering signals by using PIN diodes integrated within the antenna configuration. The presented antenna consists of square radiating stub with a pair of rotated ?-shaped slits, feed-line with an inverted U-shaped slot, and a slotted ground plane. By cutting an inverted U-shaped slot at the feed-line we can gave a new resonance at the higher frequencies that with this structure, an UWB frequency range can be achieved. In the presented antenna, we use two PIN diodes across the ?-shaped structures that by changing the ON/OFF conditions of the PIN diodes, the antenna can be used for multimode applications. In the proposed structure, when D1&D2=OFF, the UWB antenna with a single band-notched characteristic can be achieved. By changing the condition of integrated diodes to D1&D2=ON, the pair of rotated ?-shaped slits at radiating stub have been converted to four L-shaped slits that with this design the antenna can be used to generate a dual band-notched function to isolate and block any interference in the UWB frequency range.